Progress and challenges in functional nanomaterial‐based suspension array technology for multiplexed biodetection. Issue 1 (31st January 2022) - Wu, Weijie; Liu, Xinyi; Li, Wanwan
Abstract: Suspension array technology (SAT) has aroused substantial interest due to its strong multiplexed detection capability, quick binding kinetics, high throughput, and high detection sensitivity. Although rapid developments in material science have led to tremendous progress with regards to SAT, several challenges still exist that limit the performance of SAT, including limited barcode numbers, unpredictable barcode signal and suboptimal detection sensitivity. Therefore, major efforts are still needed to further improve performance to fulfill the higher requirements of precision diagnosis. In this review, we focus on summarizing recent advances regarding encoded microspheres and labels for functional nanomaterial‐based suspension array technology, then analyze the current challenges and propose corresponding solutions. We anticipate that this review will be helpful for the future design of functional nanomaterial‐based SAT platforms with superior performance. Abstract : Suspension array technology based on encoded microspheres plays a significant role in high‐throughput multiplexed detection. Two major challenges of functional nanomaterial‐based suspension array technology–limited barcoding capacity and suboptimal detection sensitivity are discussed, and an overview of possible solutions is proposed from the perspective of functional nanomaterials.